Ross Stevens and Uni Tavur: A Kiwi publishing legacy among wantoks - David Robie (Asia Pacific Network, 2019)
A pilot training project for Papua New Guinean journalists in New Zealand in 1974 ended as a failure. This led to a five-year New Zealand Government aid scheme to establish the South Pacific's first journalism school at the national University of Papua New Guinea in 1975. New Zealand journalist and broadcaster Ross Stevens was the founding lecturer and his legacy included Uni Tavur, the region's first independent newspaper produced by student journalists under an innovative ownership editing model. The UPNG programme educated a generation of journalists in Papua New Guinea and today PNG journalists have the higest level of tertiary education and training in the Pacific. The experience also had a profound impact on the traditions of free speech and journalism training for the rest of the Pacific region. This article examines the contribution made by the late Stevens and how the country's political pressures have impacted on his legacy.